PERANAN KADIN DALAM PEMBANGUNAN DI SUMATERA UTARA - Yudha Johansyah (Universitas Medan Area, 2016)
Kadin as the receptacle of communication the whole power of the business world is ready to become a partner constructive for local governments to formulate policy probisnis to be able to create a climate of business world that is more conducive and spur development daerah.mengacu to the spirit of regional autonomy ( the chamber of commerce and industry kadin ) indonesia affirmed its commitment to enhance the role of economic growth and functions in helping the region. This research is research descriptive with the approach of qualitative and an informer in this research is people being regarded as having information a lock ( key informer ) required in the area of research. The results of research obtained shows that there are 3 the role of kadin north sumatra who was the deliberation of kadin north sumatera related to revitalize the role of advocating, service and development.